Pemeriksaan Golongan Darah pada Anak dan Pemeriksaan Gula Darah pada Kelompok Usia Lanjut di Gereja Katolik Santu Petrus Pariti Kabupaten Kupang Tahun 2024 - Theresa Avila Meman; Aldiana Astuti; Muhammad Aldizar; Yoseph Maran; Mervi Berelaku (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This community service activity was conducted at the Catholic Church of Santu Petrus Pariti, Kupang Regency, involving 124 participants for blood type examinations and 69 participants for blood pressure and glucose level tests. The event began with a retreat by the Medical Laboratory Technology students aimed at raising community awareness about health. A positive response was observed through the enthusiasm of the community, who actively asked questions, indicating that they gained new knowledge related to health examinations. In blood type examinations conducted at TK Santa Maria Pariti and SEKAMI, it was found that among 18 female and 22 male children, 5 participants had blood type A, 15 had blood type B, 17 had blood type O, and 1 had blood type AB. Additionally, glucose level tests revealed that 4 participants had normal glucose levels, while 65 had abnormal levels. Blood pressure tests among the elderly showed 16 with abnormal readings and 53 with normal readings. The examination results provided an initial overview of the health status of the local community, highlighting variations in blood types, glucose levels, and blood pressure conditions. This activity is expected to enhance awareness of the importance of regular health check-ups among the community.